New approach to study the real exposure to fungi in cork industry: nasal swabs mycobiota investigation coupled with screening on fungal resistance to azoles - Viegas, Carla (2016)
The permanent contact with cork may lead to constant exposure to fungi, raising awareness as a potential occupational hazard in the cork industry.The presence of fungi belonging to the Penicillium glabrum complex has been associated with the development of respiratory diseases such as suberosis, one of the most prevalent diseases among workers from cork industries, besides occupational asthma. Azoles are used as pesticides but also the first line therapy in the treatment of Aspergillus infections; azole-resistance as been described as to have also an environmental source and is considered an emerging public health problem.The aim of this work was to characterize fungal distribution and to evaluate the presence of azole-resistant Aspergillus isolates in nose swab samples from the cork industry workers.